Complexity of linear and majority functions in the basis of antichain functions - Podolskaya, O. V. (Moscow University mathematics bulletin, 2016)
The complexity of realization of Boolean functions by circuits of functional elements in the basis consisting of all characteristic functions of antichains over a Boolean cube is studied. It is proved that the complexity of realization of an n -variable parity function is and the complexity of its negation equals the complexity of the n -variable majority function which is .